Non-communicable disease governance in the era of the sustainable development goals: a qualitative analysis of food industry framing in WHO consultations - Kathrin Lauber; Rob Ralston; Mélissa Mialon; Angela Carriedo; Anna B. Gilmore (BMC, 2020)
Abstract Background The UN system's shift towards multistakeholder governance, now embedded in the Sustainable Development Goals (SDGs), invites a broad range of actors, including the private sector, to the policymaking table. Although the tobacco industry is formally excluded from engagement, this approach provides opportunities for other unhealthy commodity industries to influence the World Health Organization's (WHO's) non-communicable disease (NCD) agenda. Focusing on the food industry, this research maps which actors engaged with WHO consultations, and critically examines actors' policy and governance preferences as well as the framing they employ to promote these preferences in the global context. Methods All written responses from food industry actors to publicly available NCD-relevant WHO consultations held between September 2015 and September 2018 were identified, totalling forty-five responses across five consultations. A qualitative frame analysis was conducted to identify policy positions expressed by respondents, as well as arguments and frames used to do so. Results Though no individual companies responded to the consultations, the majority of participating business associations had some of the largest multinational food corporations as members. Respondents overarchingly promoted non-statutory approaches and opposed statutory regulation and conflict of interest safeguards. To this purpose, they framed the food industry as a legitimate and necessary partner in policymaking, differentiating themselves from the tobacco industry and referencing a history of successful collaboration, while also invoking multistakeholder norms and good governance principles to portray collaboration as required. Respondents contrasted this with the limits of WHO's mandate, portraying it as out of step with the SDGs and framing NCD decision-making as a matter of national sovereignty. Conclusion We observed that the UN's call for partnerships to support the SDGs is invoked to defend corporate access to NCD policy. This highlights the need for more cautious approaches which are mindful of the commercial determinants of health. Systematic opposition to regulation and to governance approaches which may compromise commercial actors' insider role in global health by food industry actors shown here, and the strategic use of the Sustainable Development agenda to this purpose, raises questions about the value of collaboration from the perspective of international health agencies such as WHO.